Study of phenolic compounds in Lychnis coronaria raw materials by HPLC - Polishchuk , Yuliia; Burda, Nadiia (Annals of Mechnikov's Institute, 2023)
Introduction. Phenolic substances are compounds that exhibit diverse pharmacological activity, including antioxidant, anti-inflammatory, antibacterial, anticancer, cardioprotective activity, strengthen the immune system, etc. Therefore, the study of these compounds in the chemical composition of plants is an appropriate direction of phytochemical research. We have started studying the chemical composition of Lychnis coronaria (L.) Murray ex Desr. - a perennial herbaceous ornamental plant (Caryophyllaceae family). Foreign scientists are also conducting research devoted to the study of the chemical composition of the plant, as well as the establishment of pharmacological activity. Anti-inflammatory, anti-hemorrhoidal, anti-hepatotoxic effects have been determined for the raw material of Lychnis coronaria, as well as the prospects of using this plant in the treatment of bronchial asthma have been shown. Since phenolic compounds can participate in the development of the above pharmacological activities, it was important to study them using modern methods of analysis. In addition, the chemical composition of Lychnis coronaria, in comparison with other representatives of Caryophyllaceae family, is currently insufficiently researched and needs to be detailed. The aim of the work was the study of phenolic substances by HPLC in the raw material of Lychnis coronaria. Materials and methods. The research used herb, leaves, flowers, and stems of Lychnis coronaria, which were harvested in the flowering phase in the Kharkiv region (Ukraine) in July - August 2021/2022. To remove phenolic compounds, the raw material was extracted as follows: 0.500 g of crushed raw material was placed in a 100 ml conical flask equipped with a reflux condenser, 25 ml of 70% ethanol was added and heated in a water bath for 45 minutes. The resulting solution was then cooled to room temperature and filtered through a red tape filter into a 25.0 ml volumetric flask. The volume of the solution was adjusted to 25.0 ml with 70% ethanol. The chromatographic study of tested herb specimens was performed at a Shimadzu HPLC-system, ser.20 liquid chromatograph equipped with a diode matrix detector under the following conditions: Phenomenex Luna C18 column, dimensions: 250 mm х 4,6 mm, particle size 5 μm; column temperature 350С; detector wavelength 330 nm; mobile phase flow rate 1 ml/min; introduced sample volume 5 μl. The components were identified by their retention time and conformity of their UV spectra to standard substance. Research results. 12 flavonoids and 8 phenolic acids have been identified in the Lychnis coronaria herb. Among the flavonoids in this raw material, quercetin and rutin dominated; among phenolic acids - chlorogenic and caffeic acid. 18 compounds of a phenolic nature were identified in the leaves of Lychnis coronaria, among which 10 are flavonoids and 8 are phenolic acids. 11 flavonoids and 8 phenolic acids have been identified in the flowers of Lychnis coronaria. Apigenin dominated among flavonoids in flowers; caffeic acid prevailed among phenolic acids. 6 flavonoids and 5 phenolic acids were determined in the stems of the studied plant. Thus, it was established that the most identified phenolic compounds were in the herb, leaves and flowers of Lychnis coronaria. In addition, the quantitative content of the specified substances was higher in the above-mentioned types of raw materials, the lowest amount was observed in the stems of the studied plant. Conclusions. Therefore, the conducted studies indicate the accumulation of phenolic compounds, namely flavonoids and phenolic acids, in various parts of Lychnis coronaria. The obtained results can be used for the selection of promising raw materials of Lychnis coronaria, and also show the expediency of conducting further phytochemical research. Keywords: Lychnis coronaria (L.) Murray Ex Desr., phenolic compounds, HPLC